2011
DOI: 10.1007/s00262-011-1025-3
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 expression in melanoma cells as a possible mechanism of resistance to immune destruction

Abstract: The forkhead transcription factor Foxp3 is the only definitive marker of CD4(+)CD25(+) regulatory T cells (Tregs) and has been identified as a key regulator in the development and function of Tregs. Foxp3 expression has been reported in a variety of solid tumors, including melanoma. In this study, we validated Foxp3 expression in both tumor-infiltrating Tregs and melanoma cells by performing immunohistochemical analysis of human melanoma tissue sections. Further, we assessed Foxp3 expression in melanoma cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 32 publications
4
39
1
Order By: Relevance
“…Thus, serum autoantibodies are sensitive biomarkers for cancer detection [18]. For immune response between TAAs and autoantibodies present in cancer patients, the detection of serum autoantibodies can be used to distinguish between cancer patients and healthy subjects [19,20]. Many studies on lung, stomach and colon cancers have confirmed that TAAs and TAA autoantibodies can be used as tools for early diagnosis of cancer and indicators of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, serum autoantibodies are sensitive biomarkers for cancer detection [18]. For immune response between TAAs and autoantibodies present in cancer patients, the detection of serum autoantibodies can be used to distinguish between cancer patients and healthy subjects [19,20]. Many studies on lung, stomach and colon cancers have confirmed that TAAs and TAA autoantibodies can be used as tools for early diagnosis of cancer and indicators of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate mechanisms by which FOXP3 contributes to therapy resistance and poor prognosis include induction of immune evasion by inhibiting immune response against the tumor, promoting metastasis by regulating chemokine receptors, and downregulation of genes such as PDE3B, which is reported to prevent apoptosis of T cells [15]. Several studies in malignant melanoma, pancreatic cancer and inflammatory breast cancer have shown that FOXP3-positive cancer cells induce immune evasion by mimicking immune cells, and FOXP3-targeted immune therapy has demonstrated considerable efficacy in preclinical models [16,17]. The immune evasion property of cancer cells is receiving more attention from researchers as an emerging hallmark of cancer [18].…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in pancreatic carcinoma and melanoma cell lines, where FOXP3 expression inhibits T cell proliferation in co-culture systems [5, 8]. FOXP3 expression in tumors was also shown to be associated with worse overall survival in breast, bladder, and colorectal cancer patients [11, 22, 23].…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, FOXP3 expression has been reported in normal breast, prostate and ovarian epithelium, and to be down-regulated in the corresponding tumor tissue [2-4]. Conversely, increased FOXP3 expression has been reported in pancreatic adenocarcinoma [5], melanoma [6-8], hepatocellular carcinoma [9], leukemia [10], bladder cancer [11], thyroid carcinoma [12] and cervical cancer [13], with no expression in corresponding normal tissue. These findings suggest either a pro- or anti-tumorigenic role, depending on the tumor type.…”
Section: Introductionmentioning
confidence: 99%